2008
DOI: 10.1186/1477-7517-5-32
|View full text |Cite
|
Sign up to set email alerts
|

The perspectives of injection drug users regarding safer injecting education delivered through a supervised injecting facility

Abstract: Background: Unsafe injection practices are prevalent among injection drug users (IDU) and have resulted in numerous forms of drug-related harm including HIV/HCV transmission and other bacterial and viral infections. North America's first supervised injection facility (SIF) was established in Vancouver in order to address injection-related harms among IDU. This study sought to examine injection drug users' experiences receiving safer injecting education in the context of a SIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…Although limited in their ability to affect the physical injection setting, SEPs altered the risk environment by increasing access to material resources and safer injecting education. In comparison, PWID expressed that SIFs and selected peer-based interventions actively produced social and physical settings that enable safer practices (Fairbairn et al, 2008; Fast et al, 2008; Kerr et al, 2007; Sherman et al, 2008; Small et al, 2012a; Small et al, 2012b). For example, one participant described injecting at a SIF as “the way to do it properly…because it’s not the alley” (Small et al, 2012a, p. 315).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although limited in their ability to affect the physical injection setting, SEPs altered the risk environment by increasing access to material resources and safer injecting education. In comparison, PWID expressed that SIFs and selected peer-based interventions actively produced social and physical settings that enable safer practices (Fairbairn et al, 2008; Fast et al, 2008; Kerr et al, 2007; Sherman et al, 2008; Small et al, 2012a; Small et al, 2012b). For example, one participant described injecting at a SIF as “the way to do it properly…because it’s not the alley” (Small et al, 2012a, p. 315).…”
Section: Resultsmentioning
confidence: 99%
“…Participants commonly reported that SEIs established situations and spaces that enabled reductions in risk behaviours, such as “rushed injections” (Kerr et al, 2007; Small et al, 2012a) and syringe sharing (Fast et al, 2008; Ngo et al, 2009; Parker et al, 2012; Power et al, 2005; Spittal et al, 2004). Accordingly, these interventions were felt to increase control over the injection process (e.g., access to injecting equipment, space to inject) and minimized the impact of social, structural, and spatial barriers to safer injecting (Fairbairn et al, 2008; Kerr et al, 2007; Krusi et al, 2009; McLean, 2012; Ngo et al, 2009; Parker et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study [36] examined the education the IDUs receive from the SIFs from the perspectives of the IDUs. In this study, the narratives of Vancouver IDUs showed that they had significant knowledge gaps about safe injecting practices.…”
Section: Supervised-injecting Facilitiesmentioning
confidence: 99%
“…1 The South Bronx area, with its multiple health and other social issues in New York City may be the most well known of these problem areas in the United States; Vancouver, British Columbia's Downtown Eastside may be the most well known in Canada.…”
mentioning
confidence: 99%